Turning University/Community Partnerships into Action Through Collaboration and Communication - Todd A. Harwell (The University of Alabama, 2022)
A review of the book: Rebecca J. Dumlao (2018). A Guide to Collaborative Communication for Service-Learning and Community Engagement Partners. Sterling, Virginia: Stylus Publishing, LLC. 181 pages. ISBN: 978-1-62036-108-5